Pengaruh Leverage, ESG, dan Nilai Perusahaan Pada Sektor Pertambangan Di Indonesia: Moderasi Dewan Wanita - Michael Souw; Eriana Kartadjumena (JEMSI (Jurnal Ekonomi, Manajemen, dan Akuntansi), 2026)
The mining sector plays a vital role in Indonesia’s economy but faces challenges such as commodity price volatility, export dependency, and increasing global regulatory pressure that affect firm value. This study aims to examine the effect of leverage and Environmental, Social, and Governance (ESG) disclosure on firm value, with female board representation as a moderating variable.This research employs a quantitative approach with a population consisting of all mining companies listed on the Indonesia Stock Exchange (IDX) during 2019–2023. Samples were selected using purposive sampling based on the criteria that companies remained listed throughout the observation period, published audited annual financial statements, and consistently disclosed ESG scores. Secondary data were obtained from annual reports, the IDX database, and Refinitiv Eikon. Data were analyzed using panel regression with EViews 12. The appropriate regression model (Common Effect, Fixed Effect, or Random Effect) was determined through the Chow test, Hausman test, and Lagrange Multiplier test, followed by classical assumption testing to ensure model validity.The results indicate that leverage has a positive but insignificant effect on firm value, while ESG shows a significant negative effect. The presence of female directors does not moderate the relationship between leverage and firm value but strengthens the effect of ESG on firm value. These findings highlight the importance of inclusive governance practices and sustainability strategies to enhance the competitiveness of mining companies. Furthermore, this study contributes to the literature on ESG disclosure and board diversity in emerging markets, particularly within the context of Indonesia’s governance system, which remains influenced by patriarchal structures.